1996
DOI: 10.1021/ie950616a
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Linear Packing Model for Predicting the Porosity of Nonspherical Particle Mixtures

Abstract: Based on the similarity analysis between the spherical and nonspherical particle packings, a mathematical model, modified from the previous linear packing model for spherical particles, is proposed for predicting the porosity of nonspherical particle mixtures. The background for this development is discussed in detail. The applicability of the proposed model is validated by the good agreement between the measured and calculated results for various packing systems including binary, ternary, and multicomponent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
129
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(145 citation statements)
references
References 31 publications
(80 reference statements)
4
129
0
6
Order By: Relevance
“…In Figure 1a, the experimentally determined porosity of a binary glass bead mixture of D/d ) 10.22 (indicated by the data points, which were taken from Mota et al 2 ) is shown, together with the calculated porosity using different correction functions. 2,22,35,36 In Figure 1b, a normalized porosity ( / 0 ) is shown for data sets of Yu et al, 13 where 0 ) D 0 ) d 0 are values of 0 that correspond to those referenced in the quoted literature. It can be seen that, with decreasing δ, the smooth transition of minimum porosity (curves 1-3) may become an intersection point (data sets 4 and 5), because the filling mechanism of packing becomes predominant.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…In Figure 1a, the experimentally determined porosity of a binary glass bead mixture of D/d ) 10.22 (indicated by the data points, which were taken from Mota et al 2 ) is shown, together with the calculated porosity using different correction functions. 2,22,35,36 In Figure 1b, a normalized porosity ( / 0 ) is shown for data sets of Yu et al, 13 where 0 ) D 0 ) d 0 are values of 0 that correspond to those referenced in the quoted literature. It can be seen that, with decreasing δ, the smooth transition of minimum porosity (curves 1-3) may become an intersection point (data sets 4 and 5), because the filling mechanism of packing becomes predominant.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…4,[8][9][10][11][12][13][14][15][16][17][18][19] However, deviations of experimental data from theoretical prediction induce the development of research to seek the causes of these deviations. A linear mixture model, which is applied for binary packing when the ratio of small particle size (d) to large particle size (D) is δ ) d/D f 0, is used in numerous works.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations